ANALISIS KANDUNGAN LOGAM TIMBAL PADA TANAMAN TOMAT (Solanum lycopersicum L.) YANG DITANAM DI PINGGIR JALAN RAYA KECAMATAN AUR BIRUGO TIGO BALEH BUKITTINGGI - Sanra, Yandrilita; Hanifah, Tengku Abu; Bali, Subardi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The examination of lead metal contamination levels in tomato plants (Solanum lycopersicum L.) planted on the road side in the district Aur Birugo Tigo Baleh Bukittinggi West Sumatra has been carried out. The samples have taken at four yards randomly with a distance of 3,5 m, 20 m and 500 m from the side of the highway. The fruits and leaves of tomato and soils were destructed by using nitric acid, hydrogen peroxide and perchlorate acid and was measured using Atomic Absorption Spectrophotometric (AAS) at the wavelength of 283,3 nm. The results of analysis showed that the rate of Pb pollutants of the tomato fruit were A1 = 1,0725 mg/Kg (planted with a distance of 3,5 m from the road side); A2 = 0,9977 mg/Kg (planted with a distance of 20 m from the road side); A3 = 0,5848 mg/Kg (planted with a distance of 500 m from the road side). The concentration of Pb pollutants of the tomato leaves were B1 = 0,1983 mg/Kg (planted with a distance of 3,5 m from the road side); B2 = 0,1361 mg/Kg (planted with a distance of 20 m from the road side); B3 = 0,1370 mg/Kg (planted with a distance of 500 m from the road side); and the concentration of Pb pollutants of the soils were C1 = 2,6719 mg/Kg (with a distance of 3,5 m from the road side); C2 = 3,1039 mg/Kg (with a distance of 20 m from the road side); C3 = 2,1904 mg/Kg (with a distance of 500 m from the road side). Refferring to the Director General of Drug and Food Control (BPOM) No. 03725/B/SK/VII/89, the maximum contamination levels of metal in Food. for tomato is 1,0 mg/Kg. The maximum contamination levels of metal on the leave : 0,5 mg/Kg, refferring to the Indonesian National Standard (SNI) 7387 – 2009, the maximum contamination levels of metal on the soil is 10 mg/Kg.